1992
DOI: 10.1007/bf02245152
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of sibutramine hydrochloride, bupropion and methamphetamine on dopaminergic function: evidence that dopamine is not a pharmacological target for sibutramine

Abstract: Sibutramine hydrochloride, a novel monoamine reuptake inhibitor antidepressant, has been studied to determine whether it alters dopaminergic function in the brain. Its effects have been compared with bupropion, a dopamine reuptake inhibitor, and methamphetamine, a dopamine reuptake inhibitor and releasing agent. Sibutramine (0.1-3 mg/kg PO) and methamphetamine (0.3-30 mg/kg PO) both prevented reserpine (0.75 mg/kg IV) ptosis in rats with ED50 values of 0.6 mg/kg and 4.2 mg/kg, respectively. Bupropion (10-100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 22 publications
7
35
0
1
Order By: Relevance
“…In both animals and humans, it potently inhibits the reuptake of serotonin (5-HT) and noradrenaline, 6,7 but not dopamine. 7,8 Sibutramine represents a new class of agent for the treatment of obesity that differs from drugs such as fen¯uramine and d-fen¯uramine, which exclusively activate 5-HT systems, and from drugs such as d-amphetamine, mazindol and the b 3 -adrenoreceptor agonists, which exclusively activate catecholamine systems. 9±12 In healthy volunteers, sibutramine appears to be free from anticholinergic effects.…”
Section: Introductionmentioning
confidence: 42%
See 1 more Smart Citation
“…In both animals and humans, it potently inhibits the reuptake of serotonin (5-HT) and noradrenaline, 6,7 but not dopamine. 7,8 Sibutramine represents a new class of agent for the treatment of obesity that differs from drugs such as fen¯uramine and d-fen¯uramine, which exclusively activate 5-HT systems, and from drugs such as d-amphetamine, mazindol and the b 3 -adrenoreceptor agonists, which exclusively activate catecholamine systems. 9±12 In healthy volunteers, sibutramine appears to be free from anticholinergic effects.…”
Section: Introductionmentioning
confidence: 42%
“…9±12 In healthy volunteers, sibutramine appears to be free from anticholinergic effects. 13 It has no amphetamine-like abuse potential in either animals 8 or recreational drug users. 14 In rats, sibutramine causes a dose-dependent decrease in food intake and bodyweight.…”
Section: Introductionmentioning
confidence: 99%
“…8,14 Additionally, sibutramine has been shown to increase energy utilisation. 19,20 The increased energy utilisation activity of sibutramine may be indirectly generated by central stimulation of efferent sympathetic output to the ␤ 3 -adrenoceptors in brown adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Both preclinical and clinical studies strongly suggest that dopamine is not a target for sibutramine at pharmacologically relevant concentrations. 8,10,11,14 Consistent with its enhancement of noradrenergic activity relative to placebo, normotensive obese patients on sibutramine treatment have experienced small mean increases in systolic blood pressure (SBP) and diastolic blood pressure (DBP). Increases of 1 to 3 mm Hg and increases in pulse rate (PR) of 4 to 5 beats per minute (bpm) at doses up to 20 mg have been reported.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…In this regard, we have reported that sibutramine increased rat motor activity due to activation of the dopaminergic system in the nigro-striatum [28]. Otherwise, there is also a report that sibutramine does not have dopaminergic effects [18]. It is still unclear whether continued administration of sibutramine maintains the increase in spontaneous motor activity, as observed after acute administration, which contributes to the anti-obesity effect of sibutramine by energy expenditure.…”
Section: Introductionmentioning
confidence: 99%